Groove Pancreatitis Associated with Pancreatic Adenocarcinoma and Autoimmune Pancreatitis - Buscemi, Salvatore; D’Ambra, Marielda; Pacilio, Carlo Alberto; Panzacchi, Riccardo; Taffurelli, Giovanni; Peri, Eugenia; Ricci, Claudio; Santini, Donatella; Pezzilli, Raffaele; Casadei, Riccardo; Minni, Francesco (JOP. Journal of the Pancreas, 2012)
Context Groove pancreatitis is a chronic inflammation of ectopic pancreatic tissue within the duodenal C-loop and the head of the pancreas. Case report A 56-year-old man affected by Crohn’s disease was admitted to our Surgical Unit in 2010 for epigastric pain associated with jaundice, weight loss and vomiting. He was not an alcohol drinker. Laboratory tests revealed abnormal levels of total bilirubin (25.6 mg/dL), amylase and lipase (108 and 293 UI/L, respectively) and CA 19-9 (2,435 IU/mL). An US and a CT scan showed dilatation of common bile duct, a 30 mm iso-hypodense area in the head of pancreas involving the duodenal wall and a dilatation of the main pancreatic duct (6 mm). A FNAB revealed the presence of a poorly differentiated adenocarcinoma. Finally, a 18F-FDG PET-CT scan showed an hyperfixation (SUVmax=4.3) of the pancreatic lesion. Thus, the patient underwent a pylorus-preserving pancreaticoduodenectomy. The postoperative course was regular, with discharge in postoperative day 14th. Macroscopically, the pathological specimen showed a 50 mm multicystic paraduodenal mass and a solid 30 mm pancreatic nodule. Microscopically, the first lesion was consistent with a pancreatic hamartoma of the duodenal wall, with morphologic aspects of “groove pancreatitis”, while the solid nodule was a poorly differentiated pancreatic adenocarcinoma. Moreover, the adjacent pancreatic parenchyma was affected by a diffuse lymphoplasmacytic and eosinophilic autoimmune pancreatitis with epithelial granulocytic lesions. Five lymph nodes were metastatic (n=22), while resection margins were free. Patient is well and alive at 2 years from surgery. Conclusion A recent literature review of 348 patients with groove pancreatitis showed the association either with chronic pancreatitis (62.5%) and ductal adenocarcinoma (0.3%), separately. Our case is peculiar because the groove pancreatitis is associated with both pancreatic adenocarcinoma and autoimmune pancreatitis. Furthermore, there is no evidence that these pathologic entities could be connected each other.